Training distribution in 1500-m speed skating: A case study of an Olympic gold medalist - Orie, J.; Hofman, N.; Meerhoff, L. A.; Knobbe, A. (International Journal of Sports Physiology and Performance, 2020)
At the Olympic level, optimally distributing training intensity is crucial for maximizing performance. Purpose: The authors evaluated the effect of training-intensity distribution on anaerobic power as a substitute for 1500-m speed-skating performance in the 4 y leading up to an Olympic gold medal. Methods: During the preparation phase of the speed-skating season, anaerobic power was recorded periodically (n=15) using the mean power (in watts) with a 30-s Wingate test. For each training session in the 4 wk prior to each Wingate test, the volume (in hours), training type (specific, simulation, nonspecific, and strength training), and the rating of perceived exertion (RPE; CR-10) were recorded. Results: Compared with the 8 lowest, the 7 highest-scoring tests were preceded by a significantly (P<.01) higher volume of strength training. Furthermore, the RPE distribution of the number of nonspecific training sessions was significantly different (P<.01). Significant (P<.05) correlations highlighted that a larger nonspecific training volume in the lower intensities RPE 2 (r=.735) and 3 (r=.592) was associated positively and the medium intensities RPE 4 (r=-.750) and 5 (r=.579) negatively with Wingate performance. Conclusion: For the subject, the best results were attained with a high volume of strength training and the bulk of nonspecific training at RPE 2 and 3, and specifically not at the adjoining RPE 4 and 5. These findings are surprising given the aerobic nature of training at RPE 2 and 3 and the importance of anaerobic capacity in this middle-distance event.